The Effect of Job Satisfaction, Physical Work Environment, and Workload on Employee Loyalty at PT. Nusa Sarana Citra Bakti Suzuki Baturaja - Sindy Tria Utari; Lisa Hermawati; Dyah Ayu Putriani; Mardiah Kenamon; Tati Herlina (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the effects of job satisfaction, work environment, and workload on employee loyalty at PT. Nusa Sarana Citra Bakti Suzuki, Baturaja Branch. Employee loyalty is one of the key factors in supporting organizational sustainability and the achievement of corporate objectives; therefore, it is essential to empirically examine the factors that influence it. This research adopts a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to all 30 employees of PT. Nusa Sarana Citra Bakti Suzuki Baturaja, employing a census sampling technique. The research instrument was developed using a five-point Likert scale to measure the variables of job satisfaction, work environment, workload, and employee loyalty. The collected data were then analyzed using multiple linear regression analysis to determine the effects of each independent variable on the dependent variable. The results indicate that job satisfaction, work environment, and workload have a significant effect on employee loyalty. Higher levels of job satisfaction and a conducive work environment are able to enhance employees’ commitment and loyalty to the company, while appropriate workload management aligned with employees’ capabilities plays an important role in maintaining performance stability and loyalty. These findings suggest that companies need to pay balanced attention to both psychological and physical aspects in human resource management. Accordingly, improving employee loyalty can be achieved through management strategies that are oriented toward employee welfare. This study is expected to provide practical contributions to company management and serve as a reference for future research in the development of studies related to employee loyalty.